Knowledge management in agile organizations - Juhary Haji Ali,; Chew, Thong Giap; Tang, Tuck Cheong (Sunway University College, 2004)
It has been suggested that in the management of knowledge, organizations must be able to provide an environment in which individual and organizational knowledge, whether tacit or explicit, general or specific, declarative, procedural or causal is refined and reposited. One management process and organizational system that is of important concern in knowledge management is agility. The development of Information Communication Technology (ICT) in the era of globalization and competitive business environment indicates that agile organizations are able to better sustain in a competitive and volatile industry. By means of a case study on agility in the construction industry in Malaysia, this paper argues that knowledge management through agile organization structures can help construction firms to remain competitive in a volatile and competitive market. In conclusion, it suggests that knowledge management enables agile organizations to deal with uncertainty.